Socialization of Low Purine Diet in Elderly Patients With Gout Arthiritis at Puskesmas Batang Kuis - Panjaitan, Raini; Damayanti, Erika; Manurung, Jelita; Ginting, Wira Maria; Ginting, Raynald Ignasius (JURNAL PENGMAS KESTRA (JPK), 2023)
Gout arthritis is a disease caused by impaired purine metabolism resulting in excessive uric acid (hyperuricemia). It is said to be hyperuricemia if the uric acid level is more than 6.0 mg/dl in women and 7.0 mg/dl in men, which is measured based on blood serum. To overcome the problem of hyperuricemia, it is necessary to apply a low-purine diet, especially for elderly people with gout arthritis. The goal of a low-purine diet is to prevent monosodium urate crystals from accumulating in the joints. The implementation method used by the PkM team in collaboration with Puskesmas Batang Kuis partners and elderly people with gout arthritis consists of 4 stages. Based on the results of the activities of the 41 community service participants, frequency characteristics were obtained based on the uric acid value of the elderly at the Puskesmas Batang Kuis, namely the majority of gout categories in the elderly, namely the 7.6-9.0 category, as many as 25 people (61%). From the results of the activity it was also found that the number of elderly women with gout arthritis was more (28 people) while there were 13 men. The results of an evaluation of the increase in knowledge of 41 participants showed that the majority of elderly knowledge was categorized as good as many as 27 people (66%) participants with good knowledge. The low knowledge and understanding and awareness of the elderly regarding a low purine diet is the cause of the high number of gout arthritis sufferers. So we need a program that educates and raises public awareness and needs to monitor diet in the elderly.